Medication Experiences of Hispanic People Living with HIV/AIDS - Luz Dalia Sánchez MD, MHA, MCP, Ph.D (University of Minnesota Libraries Publishing, 2010)
Objective: The objective of this study was to describe the medication experiences of Hispanic people living with HIV/AIDS. Specific aims were to describe their current medication experiences and to describe how they viewed their medication history in order to determine essential themes for improving culturally-appropriate medication therapy management services.Methods: A qualitative, phenomenological research methodology was employed. Ten adults living with HIV/AIDS were audiotaped during semi-structured, in-depth interviews conducted in Spanish. In addition to audiotaping, field notes were taken. Thematic analysis of text was done to obtain themes consistent with the research objectives. Analysis was accomplished in two phases. The first phase applied Van Manen's lifeworld existentials of lived body, lived time, lived relation and lived space as the organizing framework for identifying themes. The second phase identified "essential themes" using holistic, selective, and detailed approaches that were applied to the themes identified in the first phase.Results: The results showed that lifeworld existentials were relevant medication experiences for Hispanic patients living with HIV/AIDS and their medication-taking behavior during their lives. Ten themes were identified. From these, we identified an overall "essential theme" comprised of: (1) Duality of Living with HIV/AIDS and (2) Primacy of Medications for Hispanic HIV/AIDS patients. Conclusions: The findings revealed that the medication taking experiences for Hispanic people living with HIV/AIDS can be described in terms of the duality of living with HIV/AIDS as "living dead" patients and in terms of the centrality that medications take in their lives, even to the point of a spiritual level.